From streets to tables: Bottom-up cocreation case studies for healthier food environments in Vietnam and Nigeria - Even, Brice; Crawford, Scarlett; Shittu, Oluyemisi F.; Lundy, Mark; Wertheim-Heck, Sigrid; Samuel, Folake O.; Talsma, Elise F.; Pastori, Giulia; Huong, Le Thi; Hernandez, Ricardo; Brouwer, Inge D.; Béné, Christophe (Elsevier, 2024)
Current food systems fail to provide equity, sustainability, and positive health outcomes, thus underscoring the critical need for their transformation. Intervening in food environments holds substantial promise for contributing to this much-needed transformation. Despite scholars and practitioners often recognizing the necessity for bottom-up approaches, there is a dearth of empirical investigations evaluating the potential of these approaches to contribute to food system transformations in low- and middle-income countries (LMICs). Our study aims to address this research gap, providing a unique perspective in this regard. Drawing on evidence from two co-creation case studies conducted with small-scale informal fruit and vegetable vendors and poor consumers in Vietnam and Nigeria from January 2020 to December 2021, we explore the relevance of bottom-up community-engaged co-creation processes in intervening within LMICs’ food retail environments. Employing a mixed-methods approach that includes quantitative surveys, qualitative interviews, participatory workshops, and focus group discussions, we demonstrate that bottom-up co-creation processes involving marginalized socioeconomic groups can generate retail-level innovations that are tailored to informal retail contexts, while remaining aligned with established top-down theories and literature pertaining to food environments and healthy diets. We provide empirical evidence highlighting how both vendors and consumers respond positively to the co-created innovations. Expanding upon our results, we offer methodological insights applicable to interventions targeted at food environments in LMICs, and considerations for future research or development initiatives in this domain. Our findings reveal the capacity of vulnerable stakeholders to actively engage in public health initiatives and contribute to developing innovative solutions that are context-specific and conducive to the adoption of healthier dietary practices. These results confirm the potential of bottom-up, co-creation, real-world interventions within informal settings to contribute towards fostering inclusive transformation of food systems.